Vascular anatomy defines sites of indomethacin induced jejunal ulceration along the mesenteric margin. Issue 6 (1st December 1997) - Anthony, A; Pounder, R E; Dhillon, A P; Wakefield, A J
Abstract : Background —Indomethacin induces ulceration in the rat jejunum with sparing of the ileum. The ulcers localise between vasa recta along the mesenteric margin of the bowel, observations that have not been fully explained. Aim —To examine the relationship between the localisation of experimental ulcers and the vascular anatomy of the rat small intestine. Methods —The normal vascular anatomy of the rat jejunum and ileum was studied and compared using arterial carbon ink perfusion. The anatomical localisation of early and advanced lesions induced by indomethacin was examined with particular reference to the vasculature. Mucosal injury induced by feeding vessel ligation for 24 hours or brief ischaemia-reperfusion injury was examined. The existence of anatomically sensitive sites to indomethacin was tested in a two dose study. Results —In the rat jejunum, poorly vascularised sites along the mesenteric margin were highly susceptible to indomethacin induced injury, such sites being absent from the ileum. Villous contraction was a feature of both early indomethacin injury and ischaemia-reperfusion injury in the rat jejunum. Twenty four hour ligation of jejunal vasa brevia selectively induced ischaemic injury along the mesenteric margin. Two doses of indomethacin to rats did not induce greater injury than a single dose. Conclusions —Results support the hypothesis that the rat jejunum possesses vascularly compromised sites along the mesenteric margin that are susceptible to indomethacin induced injury. Indomethacin may cause ischaemia-reperfusion injury selectively at these sites.